The Comparison of Quality Science Journalism in The Washington Post and The Guardian - Desmalinda, Desmalinda; Sukarno, Adam Wijoyo (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
The wave of science news related to climate change at the global level has become a trending topic of online media coverage during 2022. The purpose of this study is to determine the focus in elaborating science communication through the practice of science journalism in leading online media in the United States and the United Kingdom. The focus of the coverage moved to discuss more specific issues; the phenomenon of heat waves and global carbon. This research was conducted using a quantitative content analysis method. Data was collected through documentation of online media news content throughout 2022. The object of this research is science news articles on climate change issues in the online media The New York Times and The Guardian. The conceptual basis of this research is based on the opinion of Crystle M. Bruno (2020) who classifies the article into three parts; the introduction, the body, and the conclusion. The study found that how information is delivered in online media in the UK and America shows similarities and differences. The root of the equation can be seen in the choice of long-form journalism format. Meanwhile, differences were identified in the variations in preparing the introduction, the body, and the conclusion. More importantly, the direction and development of journalism in America and Britain is moving towards the institutionalization of quality journalism.